Twitter mood a její vliv na akciový trh - Louženský, Filip; Šimůnková, Klára; Kincl, Tomáš, 1979-; Vysoká škola ekonomická v Praze. Fakulta managementu (2023)
The aim of this work is to uncover the relationship between social media sentiment and movements in the stock markets. The study focuses on analyzing sentiment on the social media platform X (formerly Twitter), using mass tweet analysis to investigate whether a causal connection exists between the mood of social media users, extracted from short messages, and market movements. Data is obtained from the public portal Archive.org and processed using the Python programming language. Subsequently, it is analyzed using linear regression as well as Pearson, Spearman, and Kendall correlation coefficients.
Vedoucí práce: Klára Šimůnková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses